Physicochemical, functional and flow properties of a coffee husk flour - Rebolledo Hernández, María Virginia; Cocotle-Ronzón, Yolanda; Hernández Martínez, Eliseo; Morales Zarate, Epifanio; Acosta Domíngez, Laura (CIENCIA ergo-sum; Vol. 30 Núm. 3 (2023): CIENCIA ergo-sum (noviembre 2023-febrero 2024)DO - 10.30878/ces.v30n3a7, 2022)
The objective of this work was to analyze the feasibility of use coffee husk flour in food production, through the determination of its physicochemical, functional and flow properties. The results showed that coffee husk flour is rich in crude fiber (13.94 g/100 g d.s.), ash (7.86 g /100 g d.s.) and proteins (8.3 g/100 g d.s.). The flour presented good swelling capacity (9.72 g / g d.s.), oil and water retention capacity (2.41 g/g ds, 1.37 g/g d.s., respectively) and high solubility (44.7 %). So, coffee husk flour could be used in the elaboration of foods products as a source of functional components.